Concomitant Medication Usage with Levodopa‐Carbidopa Intestinal Gel: Results from the COSMOS Study. Issue 8 (28th April 2021) - Fasano, Alfonso; Gurevich, Tanya; Jech, Robert; Kovács, Norbert; Svenningsson, Per; Szász, József; Parra, Juan Carlos; Bergmann, Lars; Johnson, Anita; Sanchez‐Soliño, Olga; Tang, Zhongwen; Vela‐Desojo, Lydia
ABSTRACT: Background: Levodopa‐carbidopa intestinal gel (LCIG) is administered directly to the small intestine of patients with advanced Parkinson's disease (APD) to help maintain stable plasma levodopa levels. Objective: The objective of this study was to investigate the effect of LCIG in reducing polypharmacy for the treatment of APD. Methods: The COmedication Study assessing Mono‐ and cOmbination therapy with levodopa‐carbidopa inteStinal gel (COSMOS) is a large, real‐world, multinational observational study investigating comedication use with LCIG. All enrolled patients had used LCIG for ≥12 months and data were collected cross‐sectionally (study visit) and retrospectively. The primary endpoint was the percentage of patients using LCIG as monotherapy (without add‐on PD medications) at initiation and at 3, 6, 9, and 12 months thereafter. Results: Overall, 409 patients were enrolled from 14 countries and were treated with LCIG for a mean of 35.8 ± 23.2 months. A total of 15.2% of patients initiated LCIG as monotherapy and 31.7% were receiving monotherapy at 12 months after initiation. The mean duration of LCIG monotherapy was 39.3 ± 25.6 months. Use of add‐on medications decreased over time with all LCIG regimens. From LCIG initiation to the patient visit, mean off time decreased by 3.8, 4.6, and 3.9 hours/day for LCIG monotherapy, LCIG daytime monotherapy, and LCIG polytherapy groups, respectively, while duration of dyskinesia decreased by 1.7, 2.0, and 1.9 hours/day, respectively. Adverse events likely related to study treatment occurred in 112 patients (27.4%) during LCIG treatment. Conclusions: LCIG is an effective long‐term monotherapy option with a positive risk–benefit profile and contributes to reduced polypharmacy for patients with APD. © 2021 The AbbVie Inc. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society